El Periodo Formativo en la costa central: introducción - Kaulicke, Peter (Pontificia Universidad Católica del Perú. Fondo Editorial, 1998)
The Formative Period in the Central Coast: IntroductionThe text doesn´t have an abstract
Keywords: Arqueología; Periodo Formativo; Rutas Naturales; Arquitectura Monumental; Seriación Estilística; Archaeology; Formative Period; Natural Routes; Monumental Architecture; Stylistic Seriation; https://purl.org/pe-repo/ocde/ford#6.01.02